A study of patterns of play at High-intensity running during rugby competition - Koyanagi, R.; Kajiyama, T.; Ohtsuka, D.; Takada, M.; Sugihara, E. (The Japan Journal of Coaching Studies, 2019)
The aim of this study is to quantify the movement characteristics of High-intensity running. To achieve a goal, data from Global Positioning System were synchronized with game footage by Sportscode (Version 10.3.21), which were categorized to Source of possession and Ruck and Mauls (R/Ms). The results of this study indicate that 1) High-intensity running of BK is more than FW. Furthermore, attack situation is more than defense situation (FW:5.0 vs BK:12.0). 2) In the Source of possession, BK recorded significantly more High-intensity running than FW on Turnover and Kick in attack situation, and also Turnover in defense situation.But FW recorded more High-intensity running Restart on defense situation. 3) In R/Ms, FW recorded more High-intensity running on Restart in defense situation, BK recorded more High-intensity running on Kick and Turnover, which is transition phase of ball possession. These findings show movement characteristics of High-intensity running during rugby competition. And these findings can be used to help planning an effective training.